Tamm resonances and minibands in the models of atomic chains and superlattices - Gerasimov, O.I.; Khudyntsev, N.N. (Condensed Matter Physics, 2000)
The spectrum of the modelled regular superlattice which includes contacts is investigated using the transfer-matrix formalism. It is shown that the separated pair resonances in the chain spectrum (which are distributed in the permitted and in the forbidden zones, respectively) appear due to the existence of a single contact. The eroding of the noted minizones after making correlations between the separate regular segments in the superlattice is demonstrated. Similar resonances and minizones which can be called the Tamm resonances and minizones are considered to be useful elements for describing the surface states and zone-band structure of real systems within the restricted geometry. У роботі за допомогою формалізму трансфер-матриці розв’язана проблема обчислення спектра регулярної супергратки та запропоновано досить простий метод опису контакту в її структурі. Показано, що існування одного контакту призводить до виникнення відокремлених парних резонансів у спектрі ланцюжка, а також продемонстровано розмиття таких резонансів у відповідні мінізони після поєднання окремих регулярних сегментів у супергратку. Означені резонанси та мінізони є таммівськими та можуть виступати зручними елементами опису поверхневих станів та зонної структури реальних низьковимірних систем.